2019
DOI: 10.1111/bjh.16261
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood blast rate of clearance is an independent predictor of clinical response and outcomes in acute myeloid leukaemia

Abstract: Summary The day 14 bone marrow aspirate and biopsy (D14BM) is regularly used to predict achievement of complete remission (CR) with induction chemotherapy in acute myeloid leukemia (AML), however its utility has been questioned. Clearance of peripheral blood blasts (PBB) may serve as an early measure of chemosensitivity. PBB rate of clearance (PBB‐RC) was calculated for treatment‐naive AML patients (n = 164) undergoing induction with an anthracycline and cytarabine (7+3) and with detectable PBB at diagnosis. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In our work we aimed to integrate MRD evaluation with PBC as an added, earlier, treatment‐related biomarker previously demonstrated to be a powerful predictor of response to chemotherapy by several studies, including ours 12‐18 . First, we confirmed the prognostic value of PBC in a cohort of selected patients who achieved CR after the first induction cycle.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our work we aimed to integrate MRD evaluation with PBC as an added, earlier, treatment‐related biomarker previously demonstrated to be a powerful predictor of response to chemotherapy by several studies, including ours 12‐18 . First, we confirmed the prognostic value of PBC in a cohort of selected patients who achieved CR after the first induction cycle.…”
Section: Discussionmentioning
confidence: 59%
“…In order to anticipate information about chemosensitivity, several studies evaluated the kinetics of blast disappearance from peripheral blood (PB) after a few days of induction chemotherapy 12‐18 . Despite using different methods, all reported a clear impact of the peripheral blast clearance (PBC) on the probability of response to induction chemotherapy and survival.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinical studies have documented correlation between treatment failure and insufficient reduction of the PB blast cells at day 5 of therapy induction [6], or between complete remission and 90% of reduction in the circulating blast cells [7]. Likewise, other authors have reported that PB blast percentages at day 7 [8], determined by flow cytometry and morphologic analysis, might become a strong indicator of failure of the therapy induction [9]. However, the confidence interval of blast counting varies with the observer when assessing morphology alone [10].…”
Section: Introductionmentioning
confidence: 99%